Organochlorine pesticides application, xenobiotic metabolizing gene polymorphism and incidences of cancers in India: a review - Sharma, Khushi; Singh, Curi; Yadav, Himanshu; Kumar, Ravi; Verma, Suneet (International Journal of Research in Medical Sciences, 2023)
Excessive application of pesticides on crops has been noticed to gain maximum yield. It results in heavy damage to human health as well as environment. Pesticides application beyond permissible limit has detrimental effects on ecosystem. Organochlorine compounds are widely used as pest controller. These are considered as substantial environmental pollutant and carcinogens due to their extensive environmental release. There are sufficient numbers of studies that supports positive co-relation of organochlorine pesticides with cancer. To evaluate these detrimental effects on human health we have reviewed various studies and concluded the positive co-relation of organochloro compounds with cancers. In this study, the altered metabolism effects of organochlorine pesticides on cytochrome P450 enzyme have been observed.